Molecular Identification of Fungal Complex Associated with Stored Maize Grains Vended in Some Local Government Areas of Adamawa State, Nigeria - Peter, Patricia Sanum; Haruna, Aishatu; Abaka, AbdulAzeez Mumsiri (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Maize is a crucial global crop but remains highly vulnerable to fungal contamination, which poses serious threats to food safety and agricultural productivity. This study aimed to identify fungal species associated with maize samples from Adamawa State, Nigeria, using morphological and molecular techniques. Morphological analysis facilitated genus-level identification, while rDNA ITS sequencing provided precise species-level classification. The identified fungal species included Lichtheimia ramosa, Aspergillus latus, Aspergillus flavus, Amesia atrobrunnea, and Cladosporium cladosporioides. Among them, Aspergillus flavus was the most prevalent (48.1%), followed by A. latus (22.1%), L. ramosa (14.3%), C. cladosporioides (12.9%), and A. atrobrunnea (2.6%). Yola North recorded the highest level of fungal contamination. Growth rate analysis showed that L. ramosa exhibited the fastest growth, while A. atrobrunnea had the slowest. Molecular identification confirmed the fungal species, with ITS sequences displaying 81% to 95% similarity to reference strains. Phylogenetic analysis further clarified the evolutionary relationships among the isolates. The dominance of Aspergillus species, particularly A. flavus, raises concerns due to their mycotoxin-producing capabilities, which pose health risks and compromise food safety. While these findings align with previous reports on fungal contamination in stored grains, they differ from studies highlighting Fusarium and Penicillium as dominant contaminants in other regions. This study emphasizes the need for accurate fungal identification, improved storage techniques, and advanced molecular tools to mitigate contamination. These insights are essential for enhancing food security, promoting agricultural sustainability, and safeguarding public health in maize-reliant regions such as Nigeria.